2014
DOI: 10.1186/1880-5981-66-122
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives on thermosphere tides: 2. Penetration to the upper thermosphere

Abstract: In this paper, we present new multi-year and 72-day mean seasonal-latitudinal tidal structures in exospheric temperature derived from joint analysis of CHAMP and GRACE accelerometer measurements. These results include diurnal tides DE3, DE2, D0, and DW2 and semidiurnal tides S0, SE1, SE2, SE3, SW4, and SW6. We also employ Hough mode extensions (HMEs) and the Climatological Model of Thermosphere Tides (CTMT) to ascertain whether the observed structures are consistent with those observed at 110 km and presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 14 publications
0
40
1
Order By: Relevance
“…This tidal mode has a stronger zonal component and a weaker meridional component. Among upward propagating tidal modes, DE3 has a larger vertical wavelength allowing it to penetrate deep into the ionosphere (Forbes et al, ; Hagan et al, ). DE3 controls the electrodynamics of the equatorial E region during the months when it is stronger (e.g., He et al, ; Wan et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…This tidal mode has a stronger zonal component and a weaker meridional component. Among upward propagating tidal modes, DE3 has a larger vertical wavelength allowing it to penetrate deep into the ionosphere (Forbes et al, ; Hagan et al, ). DE3 controls the electrodynamics of the equatorial E region during the months when it is stronger (e.g., He et al, ; Wan et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Chang et al () demonstrated the generation of the westward propagating semidiurnal tide with k = 1 due to the nonlinear interaction. The origin of various nonmigrating tidal components due mostly to nonlinear interactions was discussed by Truskowski et al () and Forbes et al ().…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, Oberheide et al () revealed that SE2 and SPW4 could also form wavenumber 4 signatures. Truskowski et al () Forbes et al () noted that along with DW1, the nonmigrating tides DE3, DE2, DW2 were having strong signatures of upward propagation from lower atmospheric sources. The presence of strong tropical easterly jet during summer and fall equinox over South Asian region could not influence tidal propagation, as the tidal phase speeds are very larger than the jet velocity.…”
Section: Discussionmentioning
confidence: 99%